The Effects of Social Media on the Health of Children and Adolescents - Kubde Babita Bhikuchand,; Dr. Priya Vij, (International Journal of Scientific Research in Science and Technology, 2024)
This paper presents a comprehensive review of the existing literature on the impact of social media on the health of children and young people. Relevant studies were sourced from Medline, Embase, and PsycINFO databases to gather a well-rounded view of current findings. The research highlights that the most significant health effects of social media on children and adolescents pertain to mental health, particularly in areas related to self-esteem, overall well-being, and body image. Key issues identified include cyberbullying and the phenomenon known as "Facebook Depression," which refers to depressive symptoms triggered by social media use and social comparison. A notable association was found between frequent social media use and lower self-esteem and body dissatisfaction among young people. However, establishing direct cause and effect remains challenging, as these impacts may vary based on individual personality traits, predispositions, and social contexts. Current research primarily focuses on adolescents, with limited studies addressing the effects of social media on younger children, highlighting an area in need of further investigation. The paper underscores the necessity for more research to identify young individuals most susceptible to the potential harms of social media, as well as to develop effective risk mitigation strategies. Such research could support health-care professionals in educating parents and young people on safe and mindful social media use, promoting strategies that protect mental well-being in an increasingly digital age.
Keywords: Social Media; Children; Adolescents; Mental Health; Self-Esteem; Well-Being; Body Image; Cyberbullying; Facebook Depression; Social Comparison; Digital Health; Risk Factors; Healthcare Education; Parental Guidance; Youth Mental Health; Online Safety; Impact of Technology; Risk Mitigation Strategies